2017
DOI: 10.1155/2017/7354260
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer: From the Genetic Model to Posttranscriptional Regulation by Noncoding RNAs

Abstract: Colorectal cancer is the third most common form of cancer in developed countries and, despite the improvements achieved in its treatment options, remains as one of the main causes of cancer-related death. In this review, we first focus on colorectal carcinogenesis and on the genetic and epigenetic alterations involved. In addition, noncoding RNAs have been shown to be important regulators of gene expression. We present a general overview of what is known about these molecules and their role and dysregulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 379 publications
(331 reference statements)
0
25
0
1
Order By: Relevance
“…The results of the present study indicated that miR-612, miR-1-3p, miR-133b and miR-133a-3p may synergistically regulate SP1 expression at the translational level, and subsequently Sp1 may further adjust MMP11 and MMP14 expression at the transcriptional level to promote the invasion and metastasis of CRC. TP53 is a tumor suppressor gene, and its expression changes promote occurrence and progression of CRC (50). The data from the present study suggested that miR-155-3p and miR-612 may be involved in the regulation of TP53 expression, and may participate in the malignant development of colorectal cancer through TP53 -mediated ACTA2 and S100 calcium-binding protein A2.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicated that miR-612, miR-1-3p, miR-133b and miR-133a-3p may synergistically regulate SP1 expression at the translational level, and subsequently Sp1 may further adjust MMP11 and MMP14 expression at the transcriptional level to promote the invasion and metastasis of CRC. TP53 is a tumor suppressor gene, and its expression changes promote occurrence and progression of CRC (50). The data from the present study suggested that miR-155-3p and miR-612 may be involved in the regulation of TP53 expression, and may participate in the malignant development of colorectal cancer through TP53 -mediated ACTA2 and S100 calcium-binding protein A2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they act as gene expression regulators at the transcriptional, post-transcriptional, and epigenetic levels (21). A recent report highlighted the involvement of lncRNAs in CRC chemoresistance through several mechanisms, such as epigenetic modification, interaction with other miRNAs, acting as structural RNAs in scaffolding ribonuclear protein complexes, and regulating the expression of several genes that are involved in key cellular processes, including invasion and metastasis, apoptosis, cell proliferation and differentiation (25). Additionally, lncRNAs may be classed as competing endogenous RNAs (ceRNAs) that inhibit the targets of miRNAs; therefore, they act as miRNA sponges that regulate the migration, invasion and proliferation of CRC cells (26).…”
Section: Role Of Lncrnas In Crcmentioning
confidence: 99%
“…Several biological functions of miRNA have been reported to be related to various disease mechanisms, regulation of cellular activities and cancer progression [ 66 69 ].…”
Section: General Functions Of Mirnamentioning
confidence: 99%